Dendric Fractal Characteristics of Pores in Anthracite and Their Influences on Gas Adsorption Characteristics. (26th July 2022) - Wen, Zhihui; Jia, Bingtao; Wang, Jianwei; Ren, Jiangang; Wang, Qi
Abstract : The characteristics of pores in anthracite from Guhanshan Coal Mine in the Jiaozuo mining area were tested by the mercury injection method. According to the pore size, pores in the coal sample were classified into gas seepage pores and gas adsorption pores which were in line with the stochastic fractal model and the dendric fractal model, respectively. Besides, the fractal characteristics of adsorption pores were analyzed by using a dendric fractal model, and the influence law of the tortuosity fractal dimension D t on the gas adsorption capacity was obtained. The research results show that the amount of mercury injected into each experimental coal sample is directly proportional to its porosity, but has no obvious correlation with specific surface area. Seepage pores with sizes over 65 nm fit the stochastic fractal model, and their fractal dimension D increases with the increase of specific surface area. Adsorption pores with sizes of below 65 nm fit the dendric fractal model, and their tortuosity fractal dimension D t is positively correlated with the specific surface area. Through the gas adsorption experiment on coal samples, it is found that a larger D t corresponds to a stronger gas adsorption capacity. The research results can provide a theoretical basis for elucidating the gas adsorption characteristics of anthracite from a microscopic point of view.